Exploring the psychological landscape of thyroid nodules: resilience, anxiety, and ultrasound correlations - Wang, Jing; Wang, Lixia; Zhang, Daidi; Chen, Guoqing; Zhang, Qinfang; Chen, Haiyan; Cheng, Jiamao (Frontiers in Psychology, 2025)
BackgroundWhile thyroid nodules (TN) represent a prevalent clinical entity with ultrasound-guided management paradigms, the psychological sequelae of diagnostic imaging remain underexplored. This study investigates the complex interplay between ultrasound characteristics (C-TIRADS), psychological resilience, and anxiety manifestations in TN patients, addressing a critical gap in psychosomatic thyroidology.MethodsIn this prospective cross-sectional study, 303 consecutive TN patients (mean age 47.3 ± 12.1 years, 72.6% female) underwent standardized ultrasound evaluation using Aplio500 systems (Toshiba) at the First Affiliated Hospital of Dali University (October 2022–October 2024). C-TIRADS classifications were independently adjudicated by two radiologists. Psychological assessments employed the Hamilton Anxiety Rating Scale (HAMA) and Connor-Davidson Resilience Scale (CD-RISC) within 48 h post-examination. Advanced statistical analyses included: (1) Multivariate regression modeling accounting for demographic confounders. (2) Spearman/Kendall correlation matrices. (3) Ordinal logistic regression for malignancy risk stratification.ResultsPsychological assessments revealed that TN+ patients exhibited elevated resilience (CD-RISC total: 64.04 ± 14.166 vs. 60.61 ± 15.074; p = 0.025) but paradoxically higher anxiety levels (HAMA total: 32.51 ± 8.516 vs. 30.67 ± 8.667; p = 0.005), demonstrating a negative correlation between resilience and anxiety severity (r = −0.259, p < 0.001). Ultrasonographic analysis demonstrated significant psychosomatic associations: Higher C-TIRADS classifications predicted reduced psychological resilience (OR = 0.327, 95%CI = 0.114–0.943, p = 0.044) and increased nodule multiplicity (OR = 0.135, 95%CI = 0.034–0.537, p = 0.005). Specific ultrasound features showed differential anxiety impacts – irregular margins increased anxiety risk (OR = 362.080, p = 0.037) while capsular protrusion showed protective effects (OR = 0.003, p = 0.028). Symptom correlation analyses revealed: (1) Somatic anxiety showed stronger cardiovascular/respiratory system associations (r = 0.703–0.704). (2) Psychic anxiety correlated with cognitive-emotional domains (tension: r = 0.795; insomnia: r = 0.740). (3) Anxiety dimensions demonstrated differential resilience impacts – somatic anxiety primarily affected optimism (r = −0.146, p = 0.011), while psychic anxiety impaired overall resilience (r = −0.248, p < 0.001).ConclusionHigher C-TIRADS malignancy risk classifications were associated with reduced resilience and increased anxiety, particularly in patients with irregular nodule edges. Clinical approaches should focus on psychological support to boost resilience, treatment outcomes, and quality of life.